Relation between the Branch-to-Node Incidence and Triangular Matrices in Radial Distribution Networks - Montoya, Oscar Danilo; Gil-González, Walter; Molina-Cabrera, Alexander (Ingeniería, 2023)
The power flow solution is a classical problem in electrical engineering that has been studied for more than 60 years [1]. One of the most widely used methods corresponds to the Newton-Raphson approach, which is currently employed for analyzing power systems with meshed configurations and multiple generation sources, i.e., it is typically employed for power systems in high-voltage levels [2].